Role of crevice size induced microenvironment variation within the gap in initiating crevice corrosion of 201 stainless steel - Hao-Jing Ge; Yi-Han Bai; Hang Zhang; Hao-Ran Yuan; Ze-Jie Zhu; Pan Liu; Yun-Xiong Zeng; Jiang-Ying Wang (Frontiers in Materials)
The effects of the real-time changes in the microenvironment within the crevice caused by the change in crevice size on the induction of crevice corrosion of 201 stainless steel (201-SS) in 1 M (pH = 4.00) NaCl solution were evaluated using conventional methods and scanning electrochemical microscopy (SECM) containing potentiometric probes. Results show that a decrease in pH and an increase in the Cl− concentration within the gap are the pivotal determinants of crevice corrosion initiation. A narrower crevice creates a more aggressive corrosive environment. After immersion for 48 h, the corresponding pH values at the mouths of crevice with widths of 100, 250, 400 and 550 μm dropped to 1.64, 2.26, 2.73 and 2.88, respectively. The crevice size affects the accumulation rate of erosive ions and the initiation time of pits corrosion within the crevice, through the volume and diffusion effect. The coupling effect of the decrease in pH value and the increase in concentration of chloride ions is the main driver for the negative shift of the open circuit potential (OCP) and corrosion potential of 201-SS.